A Murine Model of Hind Limb Ischemia to Study Angiogenesis and Arteriogenesis - Yu, Jun (Methods Mol Biol, 2018)
Therapeutic angiogenesis offers promise as a novel treatment that is complementary to surgical or endovascular procedures for peripheral arterial diseases (PAD). Appropriate development and use of hind limb ischemia models is necessary for successful studies of therapeutic angiogenesis and/or arteriogenesis. In this chapter, we describe two commonly used murine unilateral hind limb ischemia models, the femoral artery transection model and the femoral/saphenous artery excision model.